Connecting With Older Adults in a Gym Environment: Perspectives of Fitness Professionals - Lucas, Patricia; Bercades, Luigi; Hammond, Kay; Power, Nicola (Human Kinetics, 2025)
Background/Objectives: As the world’s aging population increases, the importance of prophylactic measures to combat disease becomes essential. Physical activity is a protective factor against noncommunicable disease, and exercise within gym facilities is a common way for older adults to engage in it. Older exercisers consider the quality of fitness professionals (FPs) an essential factor in their motivation to participate in physical activity. This study aims to investigate the FPs’ expectations, learning, insights, and recommendations from their experiences of working with older adults in a gym environment. Methods: Participants were six gym instructors working at a facility in Auckland, New Zealand who supervise older adults in exercise classes and instruct on the use of gym equipment. They participated in semistructured interviews with a qualified research assistant. The authors utilized a pragmatic qualitative descriptive approach to the research and examined the data using inductive thematic analysis. Findings: Several broad themes were identified from the FPs’ thoughts about instructing older adults. These included social interactions and developing relationships, openness, or resistance of older people to learning; FPs’ expectations of older adults; a continuum of feelings; and professional learning and self-evaluation. Conclusion: The perceptions of FPs connecting with older adults provide insights for improving the implementation of exercise programs to increase positive outcomes from exercise among older adults. Crucial to these outcomes are relationship building and understanding the needs of older adults in a gym environment. Significance/Implications: From this study, we suggest there are opportunities for developing training courses as part of ongoing FPs’ professional development to actively encourage older adult participation in physical activity for health and well-being.
Keywords: 1106 Human Movement and Sports Sciences; Gerontology; 4206 Public health; 4207 Sports science and exercise; 5201 Applied and developmental psychology; exercise participation; professional development; exercise programs; qualitative research